Avaliação tomográfica no tratamento com Herbst em adulto jovem Computed Tomographic evaluation of a young adult treated with the Herbst appliance - Savana Maia; Dirceu Barnabé Raveli; Ary dos Santos-Pinto; Taísa Boamorte Raveli; Sandra Palno Gomez (Dental Press Editora, 2010)
INTRODUÇÃO: o aparelho de Herbst destaca-se por manter a mandíbula avançada de modo contínuo. OBJETIVO: analisar, durante 8 meses, o tratamento de um indivíduo com aparelho Herbst por meio de imagens da tomografia Cone-Beam, após o surto de crescimento pubertário (16 anos e 3 meses), portador de má oclusão de Classe II, divisão 1, associada a retrognatismo mandibular. RESULTADOS: os resultados mostraram imagens tomográficas das ATMs que sugerem remodelação do côndilo, fossa glenoide e aumento da via aérea após o tratamento com esse aparelho. CONCLUSÃO: o aparelho de Herbst é uma boa opção no tratamento da má oclusão de Classe II em indivíduos adultos jovens, pois proporciona ao paciente a correção da má oclusão e melhora da estética do perfil. INTRODUCTION: The key feature of the Herbst appliance lies in keeping the mandible continuously advanced. OBJECTIVE: To monitor and study the treatment of a patient wearing a Herbst appliance by means of Cone-Beam Computed Tomography (CBCT) images for 8 months after pubertal growth spurt. The subject was aged 16 years and 3 months and presented with a Class II, Division 1 malocclusion associated with mandibular retrognathia. RESULTS: The CBCT images of the temporomandibular joints suggest that the treatment resulted in the remodeling of the condyle and glenoid fossa and widening of the airway. CONCLUSIONS: The Herbst appliance constitutes a good option for treating Class II malocclusion in young adults as it provides patients with malocclusion correction and improves their aesthetic profile.